Research of the impact of carbon content in the auger material on its wear during dehydration in the solid waste garbage truck through regression analysis - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O.; Osadchuk, A.A. (Problems of Tribology, 2021)
The article is devoted to the study of the influence of carbon content in the auger material on its wear during dehydration of municipal solid waste in the garbage truck. Using the method of regression analysis, the hyperbolic regularities of screw wear depending on the carbon content in its material for different values of the friction path were determined. Graphical dependences of auger wear were constructed, depending on the carbon content in its material for different values of the friction path, which confirms the sufficient convergence of the obtained patterns. Carrying out additional regression analysis allowed to obtain the pattern of wear of the auger, depending on the carbon content in its material and the friction path, which established the following. After two weeks of operation and wear of the auger during the dewatering of solid waste in the garbage truck, increasing the carbon content in the auger material from 0.2% to 2.1% leads to a decrease in the energy intensity of dehydration of solid waste from 19.6% to 4.4 %, which makes the process of dehydration in the garbage truck cheaper. The graphical dependence of the reduction of energy consumption of dehydration of solid household waste due to increased carbon content in the auger material during its two-week wear is presented. The practicality of further research is to determine the rational material of the auger and ways to increase its wear resistance